‟It is by no Means Allegorical but a Simple and Straightforward Affair” : Allegory, Tangibility and Interpretation in One Story by Agnon - Stav, Shira (MiKAN, 2022)
The hermeneutics of “overt and covert” has a long history in the study of S.Y. Agnon. It is a history of reading in “layers”, with a preference for the covert, usually conceived as the key for the overall interpretation. The article seeks to sketch a different kind of relation between the overt and the covert in Agnon’s work. The case study is the beautiful short story, “At the Outset of the Day” (1952). This reading proposes to look at Agnon’s story from a horizontal perspective, constructed by “plains” of comparable value, rather than the usual hierarchy of overt and covert. I suggest doing so by taking the overt into the foreground to look at the plot of the tangible and the corporeal. The many interpretations of Agnon’s story all stressed its allegorical dimensions and hidden, concealed, message: a wish to merge with the textual and spiritual origins. However, such common interpretations prove to rush towards the fable’s moral lesson, while crudely ignoring the disturbing bodily presence at its centre: the naked body of a little girl, with her father, at a sacred place, on the most sacred day. I argue that Agnon challenges the hermeneutic method that seeks to “translate” the textual image into lucid meanings. The material dimensions of the story refuse the repression of transgressive meanings and call for a multiplicity of interpretations. In my reading, Agnon’s story challenges the distinctions between body and soul, between language and materiality, and between transcendence and immanence.